Self‐help educational booklets for the prevention of smoking relapse following smoking cessation treatment: a randomized controlled trial. (18th September 2015) - Maskrey, Vivienne; Blyth, Annie; Brown, Tracey J.; Barton, Garry R.; Notley, Caitlin; Aveyard, Paul; Holland, Richard; Bachmann, Max O.; Sutton, Stephen; Leonardi‐Bee, Jo.; Brandon, Thomas H.; Song, Fujian
Abstract: Aims: Most people who quit smoking for a short term will return to smoking again in 12 months. We tested whether self‐help booklets can reduce relapse in short‐term quitters after receiving behavioural and pharmacological cessation treatment. Design: A parallel‐arm, pragmatic individually randomized controlled trial. Setting: Smoking cessation clinics in England. Participants People who stopped smoking for 4 weeks after receiving cessation treatment in stop smoking clinics. Intervention: Participants in the experimental group (n = 703) were mailed eight booklets, each of which taught readers how to resist urges to smoke. Participants in the control group (n = 704) received a leaflet currently used in practice. Measurements: The primary outcome was prolonged, carbon monoxide‐verified abstinence from months 4 to 12. The secondary outcomes included 7‐day self#x02010;reported abstinence at 3 and 12 months. Mixed‐effects logistic regression was used to estimate treatment effects and to investigate possible effect modifying variables. Findings: There were no statistically significant differences between the groups in prolonged abstinence from months 4 to 12 (36.9% versus 38.6%; odds ratio 0.93, 95% confidence interval 0.75–1.16; P = 0.524). In addition, there were no significant differences between the groups in any secondary outcomes. However, people who reported knowing risky situations for relapse and using strategies to handle urges to smoke were less likely to relapse. Conclusions: In people who stop smoking successfully with behavioural support, a comprehensive self‐help educational programme to teach people skills to identify and respond to high‐risk situations for return to smoking did not reduce relapse.